Gerakan PELITA “Peduli Gizi Balita” Di Desa Lengkong Kecamatan Mojoanyar Wilayah UPT Puskesmas Gayaman Kab. Mojokerto - Rina Nur Hidayati; Faisal Ibnu (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
One of the health indicators that is assessed for the success of its achievement of the SDGs (Sustainable Development Goals) is the nutritional status of children under five. The family has an important role in improving and monitoring the nutritional status of children under five. The purpose of this community service is to increase the ability of families to deal with malnutrition in children under five through the PELITA Movement